IFAD Rural Finance Policy - Hans Dieter Seibel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 2000)
Two thirds of the Fund?s current projects have a rural finance component; about 21% of the Fund?s resources are dedicated to rural finance.2 Most of IFAD?s target group are small producers engaged in agric ultural and non-agricultural activities in areas of widely varying potential. Direct access to financial services affects the small producers? productivity, asset formation, income and food security. This policy paper is designed to provide an overall framework for the Fund?s work in rural finance. On that basis, operational guidelines and regional strategies will be prepared in due course for the use of staff, consultants and partner institutions, with scope both for innovations and for consolidation of successful existing practices.
Keywords: 330; Ländlicher Finanzmarkt; Entwicklungsfinanzierung; Mikrofinanzierung; Welt; Entwicklungsländer; International Fund for Agricultural Development